Modelling the electrical characteristics of Si/Transition metal oxide solar cells - Nurfadilah Asuwar (2019)
In recent years, there has been a rise in the demand for the needs of renewable energy. This comes with the increase in consumption of energy and the limitation of non-renewable energy resources. With the general aim of countries to reduce the effect of global warming and climate change, solar cell becomes an alternative to renewable energy and has the potential to reduce the effects of pollution. However, albeit the advantages of using silicon solar cells on today’s market, its high-priced may hinder the progress. The contribution of high-cost thermal budget and average efficiency may dissuade the commercial market from converting to these solar cells. However, recent research has pushed the effectiveness of solar cells with the introduction of hybrid solar cells particularly using transition metal oxides (TMO). It is found that the effectiveness of commercially available crystalline silicon (c-Si) was hindered by the several optical losses and technological limitations relating to the doped silicon [1]. Nevertheless, there have been progressive efforts in reducing the aforementioned limitations. Hence, the motivation of this report is to observe the electrical characteristics of TMO/Si solar cell using MoOX as the TMO. As such, theoretical performance of the TMO/Si solar cell will be investigated via Silvaco Atlas Software. The observed models will be the TMO/Si heterojunction modelled in Metal Semiconductor (MS) Junction and Semiconductor-Semiconductor (SS) junction. The electrical characteristics and physical characteristics of structures will be observed with simulation. Simulation is done by varying parameters on Doping of Silicon, Surface Recombination Velocity and Work Function for MS while varying of parameters of Bandgap, Electron Affinity, Doping of MoOx and Surface Recombination Velocity was done for SS. To conclude, collated experiment results are compared and observed.